2021
DOI: 10.1101/2021.07.29.454387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic identification and structural basis for the interaction between sorting nexin SNX17 and PDLIM family proteins

Abstract: The sorting nexin SNX17 controls endosome-to-cell surface recycling of diverse transmembrane cargo proteins including integrins, the amyloid precursor protein and lipoprotein receptors. This requires association with the multi-subunit Commander trafficking complex, which depends on the C-terminus of SNX17 through unknown mechanisms. Using affinity enrichment proteomics, we find that a C-terminal peptide of SNX17 is not only sufficient for Commander interaction but also associates with members of the actin-asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…Its subunits are conserved in eukaryotes from humans to single-celled choanoflagellates and are primarily localized to the outer leaflet of early endosomal compartments, where the complex is required for the plasma membrane recycling of many different cargos. Most of these, including a5b1 integrin, the amyloid precursor protein (APP) and various members of the lipoprotein receptor family such as LRP1 and LDLR, contain FxNxx[YF] sequence motifs (where F is a hydrophobic amino acid) that are recruited to Commander via the adaptor protein, sorting nexin 17 (SNX17) (6,20,(23)(24)(25)(26)(27)(28)(29). Other known transmembrane cargos such as the copper transporters ATP7A and ATP7B however, are trafficked via unknown mechanisms (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Its subunits are conserved in eukaryotes from humans to single-celled choanoflagellates and are primarily localized to the outer leaflet of early endosomal compartments, where the complex is required for the plasma membrane recycling of many different cargos. Most of these, including a5b1 integrin, the amyloid precursor protein (APP) and various members of the lipoprotein receptor family such as LRP1 and LDLR, contain FxNxx[YF] sequence motifs (where F is a hydrophobic amino acid) that are recruited to Commander via the adaptor protein, sorting nexin 17 (SNX17) (6,20,(23)(24)(25)(26)(27)(28)(29). Other known transmembrane cargos such as the copper transporters ATP7A and ATP7B however, are trafficked via unknown mechanisms (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the cargo sorting specificity is mediated by the core retromer subunit, but recent studies showed that SNX partners also participate in cargo recognition and membrane binding ( Leneva et al, 2021 ). In human, retromer complex cooperates with SNX3, SNX27, and SNX17 respectively for different cargoes ( Mcnally et al, 2017 ; Healy et al, 2021 ). For example, retromer-SNX3 recognizes the cargo through a Øx(L/M/V) motif, whereas retromer-SNX27 binds to the PDZ domain in β2-adrenoreceptor ( Lauffer et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana , counterparts for SNX3 have been recently reported, but whether they perform a similar function in plants is still unclear. In addition, no SNX27 and SNX17 homologs have been identified yet ( Healy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations